Integrating Religious Moderation Values in Arabic Language Learning at AN-NOOR Islamic Boarding School, Bandarlampung - Gunawan, Riski; Anwar, Saepul; Afyuddin, Moh Sholeh (UIN Syekh Wasil Kediri, Indonesia, 2024)
This study explores the integration of religious moderation values into Arabic language instruction at AN-NOOR Islamic Boarding School, Bandarlampung. In light of rising concerns over exclusivism and intolerance, the need to promote tolerance and peace through education has become imperative. Arabic, as a sacred language of Islam, serves not only as a medium of communication but also as a vehicle for transmitting religious and cultural values. Through a qualitative case study approach, this research investigates how Arabic language teaching is adapted to embody the principles of religious moderation, including tolerance, anti-violence, respect for local culture, and national commitment. Data were collected through interviews with teachers and students, classroom observations, and documentation. The findings reveal that Arabic teaching at AN-NOOR incorporates texts and expressions that emphasize peaceful coexistence, critical thinking, and intercultural understanding. Furthermore, the curriculum is designed to develop not only linguistic competence but also character formation aligned with Indonesia’s vision of religious harmony. This study contributes to the discourse on language education as a tool for promoting inclusive religious understanding in Islamic educational institutions.